Counseling to the Karo Regency Tourism and Culture Office for Optimizing the Selection of Tourism Routes in Karo Regency - Sembiring, Pasukat; Sofyan, Rudy (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Tourism is an effort by the Karo Regency Government to increase the potential of a region that is experiencing very rapid development. The development of tourism will have an influence on the life of the local community, that is, it can affect various aspects of life, be it social, economic, cultural, religious, language and also the environment. The extent of the influence of tourism development on aspects of life can be studied independently. In addition, tourism also plays a major role in expanding employment opportunities, encouraging activities of supporting industries, introducing natural and cultural beauty that is inseparable from a sense of increasing brotherhood in the national and international environment. This is because tourism itself creates multiple economic impacts, namely direct, indirect, secondary impacts, which provide opportunities for business growth and the role of local communities in the tourism sector. This research will discuss about determining the shortest route of tourist attractions in Karo Regency. The result achieved is the optimization of travel routes on tourist objects in Karo district so that the Karo Regency tourism office can provide more information regarding the location of tourist objects that will be traversed by local and foreign tourists.